Product Liability in a More Circular Economy : A Study of Liability for Alternative Methods of Distributing and Producing Consumer Goods - Van Gool, Elias (Université de Lille, 2024)
Specific, more strict theories of product liability, which have now largely been maximally harmonised in the EU, have developed on the basis of a linear economic model. By using doctrinal and economic legal research, this thesis examines the state of EU product liability law and how it is tested by alternative, circular economic methods of distributing and producing consumer goods, like product reuse, repurposing, resales and other retransfers, repairs, refurbishments and remanufacturing. Besides direct relevance to circular economy in the consumer goods sector, this study of so-far overlooked questions offers new theoretical insights about product liability with broader academic and practical relevance. After a general introduction to the domains of product liability and circular economy, a normative framework is developed that blends distributive justice in terms of economic efficiency with corrective justice. Subsequently, it is argued that also in a more circular economic setting a more strict product liability rule like the EU harmonisation is preferable in light of this normative framework, while the added value of product liability increases compared to its main regulatory alternatives. The thesis then studies the application to the aforementioned circular strategies of current EU product liability law based on the 1985 Directive and its almost finally adopted 2024 successor. Overall, EU product liability law turns out to be quite versatile and its relevance in a more circular consumption sector is improved by several of the new proposed rules. Nevertheless, some limitations remain and also some interpretative issues are identified in the proposed new Directive, for which amendments are proposed. Les théories spécifiques et plus strictes de la responsabilité du fait des produits, qui ont maintenant été largement harmonisées au maximum dans l'UE, se sont développées sur la base d'un modèle économique linéaire. En utilisant la recherche doctrinale et économique en droit, cette thèse examine l'état du droit européen en matière de responsabilité du fait des produits et comment il est mis à l'épreuve par des méthodes économiques alternatives et circulaires de distribution et de production de biens de consommation, comme la réutilisation des produits, le réemploi, la revente et autres retransferts, les réparations, les reconditionnements et la refabrication. Outre une pertinence directe pour l'économie circulaire dans le secteur des biens de consommation, cette étude des questions jusqu'à présent négligées offre de nouvelles perspectives théoriques sur la responsabilité du fait des produits avec une pertinence académique et pratique plus large. Après une introduction générale aux domaines de la responsabilité du fait des produits et de l'économie circulaire, un cadre normatif est développé qui mélange la justice distributive en termes d'efficacité économique avec la justice corrective. Ensuite, il est soutenu que, même dans un cadre économique plus circulaire, une règle de responsabilité du fait des produits plus stricte comme l'harmonisation de l'UE est préférable à la lumière de ce cadre normatif, tandis que la valeur ajoutée de la responsabilité du fait des produits augmente par rapport à ses principales alternatives réglementaires. La thèse étudie ensuite l'application aux stratégies circulaires susmentionnées du droit actuel de l'UE en matière de responsabilité du fait des produits basé sur la Directive de 1985 et son successeur de 2024 presque adopté. Dans l'ensemble, le droit européen en matière de responsabilité du fait des produits se révèle assez polyvalent et sa pertinence dans un secteur de consommation plus circulaire est améliorée par plusieurs des nouvelles règles proposées. Néanmoins, certaines limitations subsistent et des questions d'interprétation sont également identifiées dans la nouvelle directive proposée, pour lesquelles des amendements sont proposés.
Keywords: Accidents; Accidents de biens de consommation; Biens d'occasion; Biens de consommation; Circular economy; Commerce d'occasion; Consommateur (protection); Consumer product accidents; Product liability; Produits d'occasion; Repair; Responsabilité (droit); Responsabilité du fait des produits; Responsabilité du fait des produits (droit européen); Responsabilité du fait des services; Reuse; Réparation; Réutilisation; Second-Hand; Économie circulaire

Product Liability in a More Circular Economy : A Study of Liability for Alternative Methods of Distributing and Producing Consumer Goods - Gool, Elias van (Université de Lille ; Katholieke Universiteit Leuven, 2024)
Specific, more strict theories of product liability, which have now largely been maximally harmonised in the EU, have developed on the basis of a linear economic model. By using doctrinal and economic legal research, this thesis examines the state of EU product liability law and how it is tested by alternative, circular economic methods of distributing and producing consumer goods, like product reuse, repurposing, resales and other retransfers, repairs, refurbishments and remanufacturing. Besides direct relevance to circular economy in the consumer goods sector, this study of so-far overlooked questions offers new theoretical insights about product liability with broader academic and practical relevance. After a general introduction to the domains of product liability and circular economy, a normative framework is developed that blends distributive justice in terms of economic efficiency with corrective justice. Subsequently, it is argued that also in a more circular economic setting a more strict product liability rule like the EU harmonisation is preferable in light of this normative framework, while the added value of product liability increases compared to its main regulatory alternatives. The thesis then studies the application to the aforementioned circular strategies of current EU product liability law based on the 1985 Directive and its almost finally adopted 2024 successor. Overall, EU product liability law turns out to be quite versatile and its relevance in a more circular consumption sector is improved by several of the new proposed rules. Nevertheless, some limitations remain and also some interpretative issues are identified in the proposed new Directive, for which amendments are proposed. Les théories spécifiques et plus strictes de la responsabilité du fait des produits, qui ont maintenant été largement harmonisées au maximum dans l'UE, se sont développées sur la base d'un modèle économique linéaire. En utilisant la recherche doctrinale et économique en droit, cette thèse examine l'état du droit européen en matière de responsabilité du fait des produits et comment il est mis à l'épreuve par des méthodes économiques alternatives et circulaires de distribution et de production de biens de consommation, comme la réutilisation des produits, le réemploi, la revente et autres retransferts, les réparations, les reconditionnements et la refabrication. Outre une pertinence directe pour l'économie circulaire dans le secteur des biens de consommation, cette étude des questions jusqu'à présent négligées offre de nouvelles perspectives théoriques sur la responsabilité du fait des produits avec une pertinence académique et pratique plus large. Après une introduction générale aux domaines de la responsabilité du fait des produits et de l'économie circulaire, un cadre normatif est développé qui mélange la justice distributive en termes d'efficacité économique avec la justice corrective. Ensuite, il est soutenu que, même dans un cadre économique plus circulaire, une règle de responsabilité du fait des produits plus stricte comme l'harmonisation de l'UE est préférable à la lumière de ce cadre normatif, tandis que la valeur ajoutée de la responsabilité du fait des produits augmente par rapport à ses principales alternatives réglementaires. La thèse étudie ensuite l'application aux stratégies circulaires susmentionnées du droit actuel de l'UE en matière de responsabilité du fait des produits basé sur la Directive de 1985 et son successeur de 2024 presque adopté. Dans l'ensemble, le droit européen en matière de responsabilité du fait des produits se révèle assez polyvalent et sa pertinence dans un secteur de consommation plus circulaire est améliorée par plusieurs des nouvelles règles proposées. Néanmoins, certaines limitations subsistent et des questions d'interprétation sont également identifiées dans la nouvelle directive proposée, pour lesquelles des amendements sont proposés.
Keywords: Accidents de biens de consommation; Biens d'occasion; Circular economy; Consumer product accidents; Product liability; Repair; Responsabilité du fait des produits et du fait des services; Reuse; Réparation; Réutilisation; Second-Hand; Économie circulaire

Optimising regulatory responses to consumer disempowerment over personal data in the digital world - D'Amico, Alessia (European University Institute, 2021)
This thesis addresses the problem of individuals’ lack of control over personal data in the digital world. It sheds light on market and regulatory failures that lie behind the status quo and proposes a framework to improve regulatory responses. The two regulatory regimes that are at the core of this thesis are EU data protection regulation, which protects individuals’ fundamental rights over data, and EU competition law, which safeguards the sound functioning of the market and consumers’ economic interests. Despite the existence of these two regulatory regimes, individuals do not have sufficient control over personal data collected by digital firms, whose control over large datasets is a factor contributing to market monopolisation. The thesis argues that one reason for the shortcomings of today’s regulatory framework is that the market failure is composed of a combination of factors, which are currently addressed by the different regimes relatively independently. This dichotomy hinders the development of an effective strategy to tackle the market failure in its entirety. The approach taken in this thesis is that by integrating the two regimes, it might be possible to close the gaps deriving from a narrow perception of their regulatory spaces. Hence, the thesis formulates a holistic approach, encompassing data protection regulation and competition law, designed to increase the effectiveness of the regulatory framework as a whole. Different dimensions of the regimes’ interrelation are analysed, to uncover new ways to harness their complementarity and minimise their inconsistencies and overlaps. The thesis looks at how the regimes can incorporate elements from each other to inform their policies and application of their rules, as well as developing a complementary enforcement strategy. The holistic framework ultimately allows both regimes to better tailor their regulatory responses to the functioning of the digital market and take account of the diverse elements that constitute the market failure they seek to correct.
Keywords: Data Protection; Personal data; Privacy

Consumer protection in an electronic environment - Akhigbe, Iyen Joy (University of South Africa, 2020)
Consumer protection laws have not evolved on par with the development of electronic media. As a result, consumer protection laws do not address all major areas of legal concern that affect the electronic commerce (e-commerce) consumer. Furthermore, differing laws in the area of consumer protection make harmonised consumer protection neigh on impossible. Currently, there is a plethora of laws on the protection of consumers but most of these laws are within the sphere of conventional consumer protection legislation which does not adequately address the legal challenges posed by the proliferation of electronic transactions (e-transactions). Specific e-transaction laws are now to be found in certain international and regional documents emanating from organisations including: the United Nations (UN); the Council of Europe; the Organisation for Economic Cooperation and Development (OECD); the African Union (AU); the Economic Community of West African States (ECOWAS); the Southern African Development Community (SADC); the Common Market for Eastern and Southern Africa (COMESA); and the East African Community (ECA). These legal instruments have already been implemented in certain states’ national legislation, while other countries have yet to accede to them. Despite these legal instruments, e-commerce consumers are faced with inadequate or obsolete legislative provisions and are yet to enjoy full protection equivalent to that accorded to the “traditional” consumer. Furthermore, given the trans-national nature of the internet, divergent laws will inevitably prove to provide inadequate protection to e-commerce consumers. In this research, international and regional legislative instruments, as well as the national laws of selected countries such as the United States (US), the United Kingdom (UK), the Republic of South Africa (South Africa), the Federal Republic of Nigeria (Nigeria), and the Commonwealth of Australia (Australia) are examined. The strengths and gaps in each of these instruments and laws are identified with the aim of harmonising the principles they espouse in a single, cogent, and comprehensive body of rules which could take the form of an international convention. An international convention should be based on national and international best practices. The national adoption of the minimum standards espoused in the proposed Convention will ultimately, promote harmonisation.
Keywords: Borderless jurisdiction; Cooling-off; Cyberspace; E-agent; E-commerce consumer rights; Electronic transferable record; Hidden charges; Information; Keystroke error; M-commerce; Shrinkwrap; Single window facility; Terms and conditions; Transaction; Web-wrap; Wireless Application Protocol

Resale price maintenance in consumer good markets: an economic justification for the prohibition of RPM - Schwaderer, Melanie Ariane (European University Institute, 2019)
The thesis contributes to the debate on the EU’s approach to the business practice of resale price maintenance (RPM), which is widely criticized as too strict and in conflict with what is considered to be the consensus in the economic literature. The thesis critically dissects the economic consensus, on which the critique against the EU’s approach is based, by analyzing the empirical evidence that is cited to support the claim that RPM can frequently be explained by the service-based RPM models and shows that there is no convincing evidence that would support the significance of these positive RPM models that predict positive effects on welfare. To support this finding the thesis collects new evidence by surveying the marketing literature and shows that not only is there no convincing evidence that the positive RPM models frequently apply, but to the contrary there is evidence that these models are inconsistent with the real world phenomenon of RPM. Having refuted the service-based models the thesis takes up the scientific challenge that “it takes a theory to beat a theory” and proposes to fill the gap with three price-based models. The thesis offers an analysis of the three price-based RPM models, first from the perspective of welfare effects and then from a broader economic perspective in an attempt to ultimately show that the EU approach to RPM can be justified based on these economic models. All three models explain the situation in which RPM is used by a branded good manufacturer to create the perception of high quality, which is used either as a credible quality signal, becomes a component of the product or is used to bias the consumer decision; they thus enter the difficult terrain of consumer preference formation and of markets for the intangible components of a product.
Keywords: Competencia; Competition law; European Union countries; Marketing; Price maintenance

The realisation of rights in terms of the Consumer Protection Act 68 of 2008 - Scott, Tshepiso (University of South Africa, 2018)
The thesis examines the enforcement of consumer rights in South Africa, and is set against the backdrop of the underlying principles and theories on the enforcement of consumer protection law. It then analyses the various forms of consumer protection law enforcement mechanisms that were in place prior to the implementation of the Consumer Protection Act 68 of 2008, and sets out why there was a need for the enactment of the Consumer Protection Act. The thesis then critically discusses the consumer protection law enforcement mechanisms introduced and/or catered for by the Consumer Protection Act. The in-depth comparative analysis against the consumer protection law enforcement dispensations in both India and the United Kingdom culminates in a critical analysis of the successes and shortcomings of consumer protection law enforcement regime in present-day South Africa; as well as recommendations (in the form of legislative amendments and practical solutions) on how the South African consumer protection enforcement framework can be improved in order to facilitate the realisation of consumer rights.
Keywords: Consumer protection; Consumer rights; Enforcement mechanisms

Strict product liability in South Africa : an analysis of the concept of "defect" and the statutory defences available to the supply chain - Tennant, Sarah-lynn (University of Pretoria, 2018)
Defective products cause harm to persons and property on a daily basis. Product Liability law has accordingly evolved as a specialised area of the law of delict which seeks to prevent product accidents from happening and provides compensation in the event that defective products nevertheless reach the consumer market. Accordingly product liability regimes generally have both ex ante components such as product standards, recall mechanisms and liability provisions which are aimed at deterrence and risk-spreading as well as provisions that are applied ex post to provide redress and compensation. Designing an appropriate legal framework to underpin a product liability regime is a daunting task that involves achieving of an appropriate balance between the interests of various parties inter alia those of consumers, suppliers and the broader community. In recent decades many countries have migrated from a fault-based product liability regime to a regime which purportedly imposes strict liability on the whole supply chain. This bold move in modern product liability was pioneered in the United States who has since returned to fault-based liability for design and warning defects whilst returning strict liability in respect of manufacturing defects. After many years South Africa has joined the group of countries that applies strict liability to all defects regardless of their type. Notably the product liability regime introduced into South African law by means of the Consumer Protection Act 68 of 2008 (“CPA”) resembles the main features of the EU Product Liability Directive 85/374/EEC. The EU Model has also been taken over by Australia when they transitioned to a purportedly strict product regime in 1992. During this process the thesis also considers whether, by adopting the European model, South Africa has taken over a model which has been criticised by some American authors as outdated and based on 1965 strict product liability rhetoric as contained in section 402A of the Restatement (Second) of Torts which approach has since been discarded in the US in favour of the hybrid approach contained in the US Restatement (Third): Product Liability. This thesis focuses on product liability ex delicto. Its main aim is to interrogate and evaluate the product liability provisions contained in section 61 of the CPA, specifically with regard to the pivotal concept of defect and the statutory defences the Act has introduced. It details South Africa’s journey from the fault-based common law of product liability to the purportedly strict regime espoused by the CPA, which regimes operate parallel to each other. This is done to facilitate an understanding of the differences between the two regimes and specifically to aid interpretation and application of the product liability provisions in the CPA that deal with defectiveness and the new statutory defences. In order to obtain further guidance on how the concept of “defect” and the statutory defences in the CPA should, or could, be interpreted and applied the thesis initially considers the general foundational principles underlying product liability law and how this area of law has evolved in the United States, being the origin of modern product liability law. However, given that the South African regime of “strict” product liability ex delicto has its roots in the EU Directive and resembles some of the adapted features of the Australian product liability regime contained in the comprehensive Australian Consumer Law, the main comparative focus is on these two jurisdictions.
Keywords: Defective product; Product liability; South Africa; Supply chain

The regulation of unsolicited electronic communications (SPAM) in South Africa : a comparative study - Tladi, Sebolawe Erna Mokowadi (University of South Africa, 2017)
The practice of spamming (sending unsolicited electronic communications) has been dubbed “the scourge of the 21st century” affecting different stakeholders. This practice is also credited for not only disrupting electronic communications but also, it overloads electronic systems and creates unnecessary costs for those affected than the ones responsible for sending such communications. In trying to address this issue nations have implemented anti-spam laws to combat the scourge. South Africa not lagging behind, has put in place anti-spam provisions to deal with the scourge. The anti-spam provisions are scattered in pieces of legislation dealing with diverse issues including: consumer protection; direct marketing; credit laws; and electronic transactions and communications. In addition to these provisions, an Amendment Bill to one of these laws and two Bills covering cybercrimes and cyber-security issues have been published. In this thesis, a question is asked on whether the current fragmented anti-spam provisions are adequate in protecting consumers. Whether the overlaps between these pieces of legislation are competent to deal with the ever increasing threats on electronic communications at large. Finally, the question as to whether a multi-faceted approach, which includes a Model Law on spam would be a suitable starting point setting out requirements for the sending of unsolicited electronic communications can be sufficient in protecting consumers. And as spam is not only a national but also a global problem, South Africa needs to look at the option of entering into mutual agreements with other countries and organisations in order to combat spam at a global level.
Keywords: Anti-spam laws; Commercial electronic messages; Consumer law; Direct marketing; Electronic commerce; Electronic communications; Electronic mail (e-mail); International cooperation; Right of privacy; Spam (Electronic mail); Telemarketing; Unsolicited commercial communications; Unsolicited electronic communications

Towards responsible lending in Namibian consumer credit law : a comparative investigation - Asheela, Ndatega Victoria (University of Pretoria, 2017)
The regulation of consumer credit in Namibia mainly is provided for by the Usury Act 73 of 1968 and the Credit Agreements Act 75 of 1980. These legislative enactments originated in South Africa and were applied in South West Africa during the period of South Africa’s mandate over what is now the Republic of Namibia. Despite the fact that these enactments are over 35 years old, they are substantially unchanged. In response to an awareness of the threat of consumer over-indebtedness and other events such as financial crises, the purpose in this thesis is to undertake a situational analysis of the debt prevention measures as provided for by the Namibian legislative framework and the extent of protection these measures afford consumers in terms of irresponsible credit and over-indebtedness. A broad survey of the policies aimed at promoting responsible lending benchmarks the Namibian consumer credit regulatory framework against the leading international best principles which have been developed in response to global economic challenges. The Namibia Financial Institutions Supervisory Authority in the 2014 Microlending Bill proposes to introduce responsible lending practices in the form of a compulsory pre-agreement assessment of the prospective consumer before providing them with credit. In a comparative investigation, the creditworthiness assessment and related measures central to the responsible lending regimes in South Africa and Australia are considered. Measuring the Namibian consumer credit regulatory framework against these recent developments, it is submitted that the current debt prevention measures are inadequate in protecting consumers from irresponsible credit lending and the risk of consumer over-indebtedness. This thesis supplies reasons for the need in Namibia to update the regulatory structure of the credit industry in order to protect consumers. As a contribution to the promotion of a culture of responsible lending in the Namibian consumer credit market, the thesis proposes the introduction of responsible lending measures in Namibia’s consumer credit legislative framework.
Keywords: Consumer credit; Debt; Namibia

Consumer arbitration in South Africa and its effect on the consumer's right to redress and enforcement - Rantsane, Ditaba Petrus (University of Pretoria, 2017)
The thesis entitled "Consumer arbitration in South Africa and its effect on the consumer‘s right to redress and enforcement" notes with concern the outdated and inadequate nature of the Arbitration law currently applied in South Africa. The fact that the Act was enacted in 1965 and has never been amended highlights the desperate need to review the prevailing arbitration law with a view to aligning it with the current needs of the business world. The thesis addresses the concern that consumers are not adequately protected by the current arbitration law and thus substantially develops the discourse on the topic of arbitration in situations of unequal bargaining power. It raises three primary research questions in this context. The first question reads thus, if private arbitration is properly conducted should it still provide the parties with the envisaged benefits? Secondly, is private arbitration constitutional, especially as it impacts upon consumers‘ contracting with large corporations? Thirdly, is the private arbitration process as it is currently applied, constitutional as far as it denies parties an appeal on merits against an award that is clearly wrong? The thesis attempts to answer these questions and offer recommendations for the South African Law Reform Commission (SALRC) within the specific context of commercial arbitration. In addressing these research questions, the thesis incorporates a brief overview followed by a detailed discussion of the Arbitration law framework in South Africa and abroad. The discussion of arbitration abroad is done in order to identify best practices, which could be adapted to suit the South African environment. International Arbitration law receives attention and a few observations regarding how selected foreign jurisdictions treat arbitration. Finally, the thesis explores the possibility of establishing an independent institution that will be fully equipped to handle arbitration proceedings from inception to completion.
Keywords: Consumer arbitration; Consumer rights

Problems regarding exemption clauses in consumer contracts : the search for equitable jurisprudence in the South African Constitutional realm - Tembe, Herman C. (University of Pretoria, 2017)
Keywords: Consumer contracts; Exemption clause; South Africa

A critical review of the treatment of dominant firms in competition law : a comparative study - Munyai, Phumudzo S. (University of South Africa, 2016)
In South Africa compliance with competition law has become a major concern for firms that achieve and maintain certain levels of success and growth in the market, as their actions are often a source of complaints and litigation by rivals and competition authorities. With substantial financial penalties often levied against them for a variety of conduct deemed to constitute an abuse of their market position, dominant firms must constantly be aware of the likely impact of their business strategies and actions on both rivals and consumers. What were once thought to be normal and economically sound business practices and decisions, such as cutting prices to attract customers, have now acquired new meanings, with devastating consequences for dominant firms. So, are dominant firms under attack from competition law? In this study I aim to determine this. I track the historical development of competition law in three jurisdictions: South Africa, America, and the EU, with the aim of identifying traces, if any, of hostility towards dominant firms in the origins of competition law. I further investigate whether the formulation and enforcement of certain aspects of existing abuse of dominance provisions manifest as hostility towards dominant firms. While acknowledging the important role that competition law enforcement plays in promoting competition and enhancing consumer welfare, I conclude that significant unjustified economic and legal prejudice is suffered by dominant firms as a result of the way in which certain abuse of dominance provisions have been formulated and applied. I also offer appropriate recommendations.
Keywords: Abuse of dominance; Anti-monopoly; Anticompetitive effects; Anticompetitive harm; Antitrust law; Causation; Competencia; Competition Appeal Court; Competition Commission; Competition Tribunal; Competition law; Consumer harm; Consumer welfare; Counterfactual; Dominant firms; Exclusionary conduct; Hostility; Monopoly; Super-dominant; Unilateral conduct

Collective action in comparative and empirical perspective: towards a socio-legal theory - Fortes, Pedro Rubim Borges (University of Oxford, 2016)
This DPhil thesis enhances existing understandings of collective action through a comparative and empirical study. Empirical analysis of economic, political, juridical, and social dimensions of the Brazilian experience reveals that some central understandings in existing literature are not borne out in this empirical context. In particular, the assertion that low monetary incentives for individuals hinder growth in use of collective action is strongly challenged. The Brazilian experience is contextualised through comparative analysis of three legal traditions of collective action: class actions; collective redress; and civil public actions. The Brazilian system presents a setting with potential for regulatory enforcement of consumer protection law, but rare episodes of consumer compensation or the imposition of punitive damages on corporations. With low monetary incentives, the growth of collective actions is explained by non-monetary incentives and investment in social capital through development of institutional trust and legal institutions. Collective actors develop their organisational infrastructure and perform their roles as representatives through institutional dynamics of concentration, competition, cooperation, and deference. The coexistence of multiple institutional actors in the regulatory space reduces agenda control, increases opportunities for consumer participation, and increases oversight of regulatory capture. The categories of diffuse, collective, and homogeneous individual rights explain the role of law in establishing procedural pathways and special features. This study is broadened through analysis of the legal environment and the potential regulatory impact of collective actions on the social relationships between businesses and consumers. I also evaluate limitations and possibilities regarding access to justice, judicial economy, compensation, and deterrence. This thesis indicates the possibility of developing a socio-legal theory of collective action, which would enhance our understanding of the complex dynamics at play by going beyond analysis of the consumer experience as merely an economic transaction or a legal object, analysing them instead as a complex social relationship.
Keywords: Collective action; Consumer (protection); Consumer compensation; Droit de la consommation

The Regulation of Promotional Competitions in South Africa - Strachan, Daniel Petrus (University of Pretoria, 2016)
Promotional competitions are competitions in which prizes are awarded by lot or chance in order to promote goods or services. Due to the chance element, these competitions are often categorised as lotteries or gambling. Initially, South African legislation did not make provision for the running of promotional competitions, but this situation changed when the Lotteries Act, 1997 came into force. Currently, promotional competitions are regulated by the Consumer Protection Act, 2008 (CPA). This thesis examines the regulation of promotional competitions in South Africa. It commences with a background discussion, which touches on the relevant terminology and some sociological aspects. It then considers the consequences of gambling and the need for and nature of regulation, and deals with the marketing and consumer protection contexts. This is followed by a brief overview of the global and South African history of gambling, lotteries and promotional competitions, which includes a discussion of South African case law. Foreign law relating to promotional competitions in New Zealand and Great Britain is explored in order to compare this to the South African position. This is followed by an examination of the current regulation of promotional competitions in South Africa, including a discussion regarding the interplay between the CPA and the Lotteries Act and a detailed analysis of the CPA’s provisions. The self-regulation of promotional competitions is discussed as well. The concluding chapter of this thesis contains recommended solutions for the problems identified in the analysis of the relevant legislation.
Keywords: Competencia; Competition law; Concurrence (droit); Consumer law; Droit de la consommation

The impact of the unfair commercial practices directive (2005/29/EC) on contract law - Đurović, Mateja (European University Institute, 2014)
This thesis examines the relationship between the law on unfair commercial practices and consumer contract law. The thesis develops the claim that Directive 2005/29/EC, on unfair commercial practices (UCPD) has had a strong impact on the content of consumer contract law, despite the declaration concerning the independence between both branches of law contained in Article 3(2) UCPD. In order to substantiate this claim, the thesis examines the implications for consumer contract law of the main components of the regulatory regime laid down by the UCPD, namely, (1) the notion of average consumer, (2) the duty to trade fairly, (3) the duty of information and (4) the remedies. By looking both at the theoretical underpinnings and at the actual operation of this regulatory regime, the thesis casts light on the way in which the UCPD has shaped consumer contract law. The thesis further shows that this is an ongoing phenomenon whose ramifications may be far-reaching, for it implies that the UCPD is powerfully fuelling the Europeanization of contract law.
Keywords: Consumer protection; Contracts; European Union countries

The action for injunction in EU consumer law - Ogorzałek, Magdalena (European University Institute, 2014)
In 1998 the European Union adopted a new self-standing instrument of collective enforcement - the Action for Injunction. Until then, the main focus was on the improvement of the position of the individual consumer through the adoption of substantive consumer law directives. The Injunction Directive provides for a general framework on consumer law enforcement in national and cross-border litigation. Qualified entities, public agencies and/or consumer organisations, are granted legal standing. National courts are bound to mutually respect the standing of EU wide registered qualified entities. Outside these clear-cut rules on the mutual recognition of standing, the Injunction Directive remains largely silent. The implementation into 28 Member States swiftly revealed the rather limited harmonising effect. The thesis investigates and explains how despite the legally approved diversity, the Injunction Directive contains the potential to turn diversity into convergence. The key to understanding the potential is the thesis of dualism of enforcement measures. Read together with the Annex the Injunction Directive establishes the deep interconnection between collective and individual enforcement, of substantive and procedural enforcement, of judicial and administrative enforcement. The different levels and means of enforcement should not be regarded separately but should always be looked at in their interplay, in their mutual institutional design and their mutual impact. Evidence for convergence can be found in the Invitel judgment of the ECJ and in the practice of consumer organisations via co-ordination actions across borders by which they overcome the boundaries of collective vs. individual or judicial vs. administrative enforcement. Regulation 2006/2004 re-adjusts the dualistic structure of enforcement in favour of public bodies and promotes convergence through para-legal means, through new modes of enforcement, through co-operation and co-ordination outside courts and in open interaction between administrative bodies, to which consumer organisations are admitted on approval only.
Keywords: Consumer protection; European Union countries; Injunctions

The influence of the Consumer Protection Act 68 of 2008 on the common law of sale - Barnard, Jacolien (University of Pretoria, 2013)
The purpose of this thesis is to investigate to what extent the Consumer Protection Act 68 of 2008 (CPA) influences the common law of sale in South Africa. “Common law of sale” refers to the essentialia of sale (the minimum characteristics that parties must have consensus on to conclude a valid sale). The parties must have consensus on the intention to buy and sell, the things sold and the purchase price. The common law of sale also refers to the common law duties of the parties, the duties of the seller in particular (conversely therefore the rights of the buyer). The primary duties of the seller which will be investigated are: a. the duty of safe-keeping (including and investigation into the passing of benefit and risk doctrine); b. the duty of delivery and transfer of ownership; c. the warranty against eviction; and d. the warranty against latent defects. The primary common law duties of the buyer to pay the purchase price and accept the thing sold are included in the investigation as well. The formalities required in certain sale agreements, that wording must be in plain language as well as the buyer’s cooling-off rights are also investigated. An investigation into the influence of the CPA on the common law of sale in South Africa warrants a systematic framework and modus operandi which are: a. an investigation into the historical background of the common law of sale and its principles in the Roman law and Roman-Dutch law; b. a critical analysis of the position where the CPA is not applicable (the common law position); c. an extensive analysis and critical evaluation of the relevant provisions of the CPA and the influence thereof on the common law of sale; d. a comparative analysis of the appropriate provisions in Scotland and Belgium; e. a conclusion of the influence of the CPA on the common law of sale (whether the particular common law of sale principle is confirmed, amended or excluded in terms of the Act); and f. recommendations (taking into account the comparative analysis) regarding the rectification of uncertainties and ambiguities that arose as a result of the investigation. It is also important to remember that the existing principles of the common law of sale will still be applicable for transactions and agreements which fall outside the application of the Act. The golden rule to keep in mind when investigating the influence of the CPA on the common law of sale is to determine which approach and interpretation will be most beneficial to the consumer.
Keywords: Common law of sale; Consumer Protection Act; South Africa

The concept ‘fairness’ in the regulation of contracts under the Consumer Protection Act 68 of 2008 - Stoop, Philip Nicolaas (University of South Africa, 2013)
The thesis analyses the concept ‘fairness’ in consumer contracts regulated by the Consumer Protection Act 68 of 2008, mainly from the perspective of a freedom and fairness orientation. It discusses the evolution of ‘fairness’ as background to a more detailed discussion of the classification of fairness into substantive and procedural fairness. The thesis examines dimensions of fairness, factors which play a role in the determination of fairness, and fairness- oriented approaches in an attempt to formulate a framework for fairness in consumer contracts. The main aspects that should be taken into account to justify a finding of fairness, or to determine whether a contract is fair, are identified. This analysis addresses, too, the extent to which the fairness provisions of the Consumer Protection Act are appropriate (with reference to the law of South Africa, Europe, and England).
Keywords: Consumer contracts; Consumer protection law; Contracts; Contractual fairness; Freedom of contract; Law of contract; Liberty of contract; Procedural fairness; Standardized terms of contract; Substantial fairness

A Proposed discharge dispensation for consumer debtors in Tanzania - Maghembe, Ngwaru Jumanne (University of Pretoria, 2013)
The Tanzanian private sector is growing, partly due to the state’s efforts to conform to the global economy. As the economy expands and the National Microfinance Policy of 2001 is realised, more and more credit has been made available to consumers. As a direct consequence of the increase of credit, the number of over- indebted consumers in Tanzania is on the rise. The current debt relief system is regulated by the Tanzanian Bankruptcy Act no. 9 of 1930, a piece of colonial legislation. Unfortunately this law is ineffective, costly and outdated. Some of the problems identified in this study with this debt relief regime include the lack of a cost- effective alternative to bankruptcy and its total reliance on the judiciary, an institution that is itself overburdened and requires reform. The purpose of this study is to make recommendations for the reform of the current debt relief system and propose a debt relief dispensation for consumer debtors in Tanzania that will efficiently cure over- indebtedness. A wide comparative investigation was undertaken in this study of selected common law, civil and mixed legal systems that have substantial experience with the boom in over-indebted consumers now facing Tanzania. A number of solutions were borrowed from these systems that may potentially solve Tanzania’s debt relief problem. One of the main findings of this thesis is that, over time, developed jurisdictions that rely on credit in the private sector appear to be converging on the same type of procedures and moderate philosophies for consumer debt relief. These include less judicial supervision for debt relief procedures, less freedom of choice for over-indebted consumers when it comes to the type of procedures available, and mandatory surplus income repayments for debtors who can afford it. In order to address the problems of the Tanzanian debt relief system, this thesis proposes a complete overhaul of the administration of debt relief procedures in Tanzania and the introduction of a combined alternative to bankruptcy that consists of three joint procedures. A number of amendments are also proposed for the Bankruptcy Act no.9 of 1930. This thesis states the status of legal developments as they were in the selected jurisdictions on 31 December 2012.
Keywords: Bankruptcy Act; Current debt relief system; Tanzania

A Critical Examination of Consumer Protection Law and Practice in Nigeria - Nwanne, Monye Felicia (University of Lagos, 1998)
This work considers two broad aspects of consumer law, namely, substantive and practical protection of consumer rights. The former examines the law on consumer protection as contained in the statute books and judicial decisions. The latter deals withthe law in practice. This considers the practical implementation of the various laws on consumer protection by the operative agencies. It also examines the practical effects of these laws on the level of consumer protection. The work is divided into ten chapters.Chapter one gives a survey of consumer protection in different jurisdictions. It also states the research problems, objectives of the study, hypotheses, scope, signi ticance of the work, conceptual frame work and literature review.Chapter two discusses the methodology adopted in this work. Chapter three considers the laws gov.erning dealings in regulated products. These products are food, drugs, cosmetics, medical devices, bottled water, chemicals and hazardous products. It is seen from this chapter that the law makes reasonable provtsfc;ns on the control of regulated products. In contrast, the level of practical protection bas remained low due to weak enforcement system.Chapter four examines the laws which impose further restrictions on dealings in drugs. This reveals that the law adequately controls dealings in drugs . But like the case of laws considered in the preceding chapter, implementation of the statutory provisions remains a problem.Chapter jive examines the functions and activities of the Standards Organisation of Nigeria whose duty it is to prescribe and ensure compliance with product standards. Like the cases of the agencies discussed in the previous chapters, a major problem facing the organisation is the ineffective implementation of its standards.Chapter six discusses the civil liability of an offender to the victim. This chapter reveals that a person whose product causes injury to the person or property of another, is civilly liable to that other person. His liability is without prejudice to his criminalliability. Chapter seven examines the course of action open to a claimant who is not in privity of contract with the defendant. This chapter reveals that such a claimant can sue in the tort of negligence. But his chances of success are greatly limited by the restrictive meaning accorded the term "product defect" in tort law. Proof of negligence also constitutes an almost insurmountable obstacle. The chapter concludes that as a way of getting round the problem of proof of negligence, there is need to introduce strict product liability in selected cases particularly in the fields of pharmaceuticals and articles of food. Chapter eight examines the contractual rights of a consumer/purchaser. This chapter shows that action in contract is of immense benefit to the claimant because he does not have to prove negligence on the part of the other contracting party. In addition, liability is strict since an exercise of due care will not absolve the offender. But this course of action is of limited application because it is not available ta a consumer who is not also the buyer of the product. This chapter concludes like the preceding one that the only solution ta the basic contract requirements is the introduction of strict liability in selected areas. Chapter nine analyses the data on the practical implementation of consumer laws, while chapter ten summarises our research findings and proffers some suggestions.
Keywords: Consumer (protection); Law; Nigeria